1997
DOI: 10.1046/j.1365-2826.1997.00556.x
|View full text |Cite
|
Sign up to set email alerts
|

Activational Effects of Gonadal Steroids on Hypothalamo‐Pituitary‐Adrenal Regulation in the Rat Disclosed by Response to Dexamethasone Suppression

Abstract: Previous studies demonstrated that gonadal steroids secreted during perinatal life permanently 'organize' the mechanisms governing hypothalamo-pituitary-adrenal (HPA) function, leading to sexually differentiated patterns of pituitary-adrenal activity under basal and stress conditions. In this paper, we show that gonadal steroids can also exert 'activational' effects upon the HPA system. Examination of the ability of different doses of dexamethasone to suppress the nocturnal increase in corticosterone secretion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 5 publications
4
21
0
Order By: Relevance
“…3␣,5␣-THP also reduces ictal activity induced by perforant path-way stimulation (Frye, 1995) and that seen in seizureprone animals (Finn, Roberts, & Crabbe, 1995). The present finding that prenatally stressed females were less sensitive to exogenous 3␣,5␣-THP is consistent with these previous findings and others which show that females are particularly vulnerable to prenatal stress and variations in 3␣,5␣-THP (Almeida, Canoine, Ali, Holsboer, & Patchev, 1997;Devaud, Purdy, Finn, & Morrow, 1996;Devaud et al, 1995;Morrow, Devaud, Purdy, & Paul, 1995;Patchev, Hassan, Holsboer, & Almeida, 1996).…”
Section: Discussionsupporting
confidence: 91%
“…3␣,5␣-THP also reduces ictal activity induced by perforant path-way stimulation (Frye, 1995) and that seen in seizureprone animals (Finn, Roberts, & Crabbe, 1995). The present finding that prenatally stressed females were less sensitive to exogenous 3␣,5␣-THP is consistent with these previous findings and others which show that females are particularly vulnerable to prenatal stress and variations in 3␣,5␣-THP (Almeida, Canoine, Ali, Holsboer, & Patchev, 1997;Devaud, Purdy, Finn, & Morrow, 1996;Devaud et al, 1995;Morrow, Devaud, Purdy, & Paul, 1995;Patchev, Hassan, Holsboer, & Almeida, 1996).…”
Section: Discussionsupporting
confidence: 91%
“…on the increase in CORT secretion in the late afternoon; as previously reported [36], this dose submaximally suppresses nocturnal CORT levels in male rats. Blood samples for the determination of basal CORT secretion were collected between 6 and 7 p.m.; DEX was injected intraperitoneally at noon on the following day, and CORT levels were measured in samples withdrawn 6 h later.…”
Section: Methodssupporting
confidence: 82%
“…Briefly, this conclusion is based on the findings that in rats receiving MEL (i) restoration of basal CORT secretion after stress occurred faster than in control animals, (ii) nocturnal elevation of CORT was strongly attenuated by a low dose of DEX (20 µg/kg) which is known to be ineffective in intact male rats (c.f. Almeida et al [36]; see also fig. 3 in this study), (iii) the basal release of pituitary ACTH in vitro was significantly decreased as compared to controls and (iv) CRH alone was unable to stimulate pituitary ACTH secretion (fig.…”
Section: Discussionmentioning
confidence: 99%
“…This effect appears related to high glucocorticoid receptor occupancy, rather than downregulation of physiological glucocorticoid levels with the HPA axis, and is mimicked by the pure glucocorticoid receptor agonist, RU28362, at high dosage (Stokes & Sigmund 1998). The dose of dexamethasone used in our study was more than 10-fold lower and, although this dose strongly downregulated the HPA axis, as expected (Almeida et al 1997), there was little influence on ENaC mRNA expression. In vitro physiological glucocorticoids bind mineralocorticoid receptor with an affinity equal to that of aldosterone, and circulate in 100-1000-fold excess over aldosterone.…”
Section: Discussionsupporting
confidence: 56%
“…Mice in group 2 received dexamethasone in a dosage that causes modest glucocorticoid excess and suppression of the hypothalamic-pituitary-adrenal (HPA) axis and corticosterone concentrations (Almeida et al 1997), and thus 'substitutes' dexamethasone for corticosterone. Group 3 received aldosterone; previous studies using high doses, and our preliminary work, indicated the aldosterone dosage used in adrenal-intact animals would cause an approximately threefold increase in mean plasma aldosterone concentrations.…”
Section: Methodsmentioning
confidence: 99%